Exploring the potential location of future earthquakes in Harrat Lunayyir, Western Saudi Arabia - Ali Abdelfattah; Chokri Jallouli; Hassan Alzahrani; Saleh Qaysi; Mohammed Fnais; Abdullah Al-Amri (All Earth)
The Arabian Shield constitutes the eastern flank of the Red Sea and features zones rich in lava flows potentially associated with seismic activity. Notably, the Harrat Lunayyir (HL) seismic dislocation zone in the shield experienced a prominent earthquake swarm in 2009, representing seismic activity that may have induced subsequent Coulomb stress changes and gravity anomalies. Integrating analyses of gravity anomalies, earthquake characteristics, and Coulomb stress transfers were performed to explore the variations in static stress and depth-dependent crustal heterogeneities. The spatial distribution of hypocentres, seismic moment, focal mechanisms, and frictional properties demarcates the weakness subzone in HL bordered by hardness zones. Coulomb stress analysis identified positive stress patterns aligned with a north-northwest (NNW) trend, parallel to the Red Sea rift axis, while negative stress patterns were distributed both eastward and westward. Gravity modelling highlighted crustal heterogeneities with low-density areas corresponding to the seismic activity zone and high-density regions in the surrounding vicinity. A significant correlation between observed anomalies and the NNW faults elucidates the regional tectonic processes within the Red Sea rifting system. The highlighted fault segments and depth-dependent crustal heterogeneities may pose considerable seismic hazard potentials in the region, emphasising the necessity for ongoing monitoring and assessment.